Peran Komunitas Gereja terhadap Peningkatan Self Awareness untuk Mencegah Peningkatan HIV/ AIDS: Kajian Literatur [Role of the Church Community in Increasing Self Awareness to Prevent an Increase in HIV/AIDS: Literature Review] - Elysabeth Sinulingga; Agung Waluyo; Sri Yona (Nursing Current: Jurnal Keperawatan, 2021)
Background: People infected with HIV (PIWH) are increasing in number in Karo Regency every year. Therefore, all sub-districts or villages contribute the incidence of HIV / AIDS. While the HIV prevention program already exists at KPA GBKP (Commission on HIV /AIDS Prevention of Batak Karo Protestant Church) but has not seen its effect. Methods: Literature review are conducted using the PRISMA model. All studies reviewed were quantitative, with most studies using cross sectional studies (14.29%), using literature reviews (9.52%), using experiments (28.57), using quasi experiments (33.33%, and using Randomized Control Trial/RCT (14.29%). Sample sizes varied from 134 to 1444 participants. The dependent variable is HIV/AIDS prevention. Independent variables are church members, family support, and increased self-awareness. Of the 1173 articles, 21 that met the inclusion and exclusion criteria were selected for the study. The articles were collected from 4 database sources including Proquest, EBSCO-CINAHL, Springer Link and Google Scoler. Result: HIV/AIDS prevention was influenced by self awareness (18.1%), church members (9%), family support (54.5%), and interventions to prevent HIV/AIDS (27.2%). Although some countries had revealed that the promotion of HIV/AIDS health and prevention was improved and the concern of all communities to reduce the stigma of HIV/AIDS. Conclusion: Increased HIV/AIDS prevention was influenced by the role of church members, community, family support, and increased self awareness.BAHASA INDONESIA ABSTRAK: Latar Belakang: Orang yang terinfeksi dengan HIV (ODHA semakin meningkat jumlahnya di Kabupaten Karo setiap tahun. Oleh karena, semua wilayah kecamatan atau desa ikut menyumbangkan angka kejadian penyakit HIV/AIDS. Sementara program pencegahan HIV sudah ada dilakukan di KPA GBKP (Komisi Penangulangan HIV/AIDS Gereja Batak Karo Protestan) tetapi belum terlihat pengaruhnya. Metode: Kajian literatur dilakukan dengan menggunakan model PRISMA. Semua studi yang ditinjau adalah kuantitatif, dengan sebagian besar studi menggunakan studi cross sectional (14,29%), menggunakan tinjauan literatur (9,52%), menggunakan eksperimen (28,57), menggunakan quasi eksperimen (33,33%, dan menggunakan Randomized Control Trial/RCT (14,29%). Ukuran sampel bervariasi dari 134 hingga 1.444 peserta. Variabel dependen adalah pencegahan HIV/AIDS. Variabel yang tidak tergantung adalah anggota gereja, dukungan keluarga, dan peningkatan self awareness. Dari 1.173 artikel, 21 artikel yang memenuhi kriteria inklusi dan eksklusi yang dipilih untuk penelitian ini. Artikel-artikel tersebut dikumpulkan dari 4 sumber basis data meliputi Proquest, EBSCO-CINAHL, Springer Link dan Google Scoler. Hasil: Pencegahan HIV/ AIDS dipengaruhi oleh self awareness (18,1%), anggota gereja (9%), dukungan keluarga (54,5%), dan intervensi untuk mencegah HIV/AIDS (27,2%). Meskipun beberapa negara telah mengungkapkan bahwa promosi kesehatan dan pencegahan HIV/AIDS ditingkatkan dan kepedulian semua masyarakat untuk mengurangi stigma HIV/ AIDS. Kesimpulan: Peningkatan pencegahan HIV/ AIDS dipengaruhi oleh peran anggota gereja, komunitas, dukungan keluarga, dan peningkatan self awareness.